Portrait of Human Rights and Islam: An Analysis of Development, Theological Responses, and Contemporary Applications - Mahabbati, Suci; Ohira, Norman; Patrah, Ideal; Malik, Khairil (AJIS: Academic Journal of Islamic Studies, 2023)
Human rights issues have become an interesting debate in the dynamics of the current world political arena. Western countries use human rights issues as a political instrument against other countries, especially Muslim countries. The reality of the concept of universal human rights comes from natural law. Long before the declaration of universal human rights, the Prophet Muhammad (PBUH) had issued the charter of Medina, which was full of human rights values. The formulation of universal human rights and Islamic human rights is hardly different. In fact, it can be said to be complementary. This paper uses a descriptive-analytical method, namely, by explaining the description of the data found and analyzing it so that the results and findings of this paper can be holistic, concise, and philosophical, and can be scientifically proven based on existing reality. This paper finds that in the Islamic world, the concept of human rights aims at the benefit (maqāṣid al-sharī'ah). However, there are differences between Universal and Islamic human rights, such as the concept of women's freedom and heritage. This difference has an impact on the concept of specific human rights or relative human rights, which are limited by the culture and sociology of certain societies, especially religions that cannot be equated. The Islamic world's response to universal human rights conceptually considers that universal human rights are different from Islamic human rights principles, universal human rights are not based on religious (secular) values. Some Muslim countries are against directly rejecting and using Islamic human rights completely, such as in Iran and Saudi Arabia; and some of them accommodate universal human rights. In the Islamic world, the implementation of human rights is influenced by global political factors with the imposition of Western double standards on Muslim countries, accompanied by economic, military and media forces to pressure Muslim countries. This causes the human rights problem in Muslim countries to be not completely resolved and gives rise to a strong resistance movement to Western human rights (Islamic fundamentalism).